Curriculum Mapping of the Master’s Program in Pharmacy in Slovenia with the PHAR-QA Competency Framework - Gmeiner, Tanja (Pharmacy (Basel), 2017)
This article presents the results of mapping the Slovenian pharmacy curriculum to evaluate the adequacy of the recently developed and validated European Pharmacy Competences Framework (EPCF). The mapping was carried out and evaluated progressively by seven members of the teaching staff at the University of Ljubljana’s Faculty of Pharmacy. Consensus was achieved by using a two-round modified Delphi technique to evaluate the coverage of competences in the current curriculum. The preliminary results of the curriculum mapping showed that all of the competences as defined by the EPCF are covered in Ljubljana’s academic program. However, because most EPCF competences cover healthcare-oriented pharmacy practice, a lack of competences was observed for the drug development and production perspectives. Both of these perspectives are important because a pharmacist is (or should be) responsible for the entire process, from the development and production of medicines to pharmaceutical care in contact with patients. Nevertheless, Ljubljana’s graduates are employed in both of these pharmaceutical professions in comparable proportions. The Delphi study revealed that the majority of differences in scoring arise from different perspectives on the pharmacy profession (e.g., community, hospital, industrial, etc.). Nevertheless, it can be concluded that curriculum mapping using the EPCF is very useful for evaluating and recognizing weak and strong points of the curriculum. However, the competences of the framework should address various fields of the pharmacist’s profession in a more balanced way.